Pengembangan Bahan Ajar Menulis Esai Dengan Memanfaatkan Kearifan Lokal Melalui Pembelajaran Berbasis Proyek (PBP) Siswa SMA - Sutriyati; Widyatmike Gede Mulawarman; Yusak Hudiyono (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2019)
The purpose of research for the development of teaching materials to write essays with local wisdom through PBP in grade XII high school students. The scope of this development is limited only to the development of teaching materials, development of learning tools and effectiveness in the learning process. The method used in this research is Research and Development (R&D), using development research design with Brog & Gall model. Source of data that become object in this research is student of class XII in SMA Negeri 9 Balikpapan. Development of teaching materials obtained by the material expert test results 82% declared feasible, 84% media expert test declared feasible, 85% design assessment test declared feasible, field test 72.3% small group declared good, a field test of large group 79.6% expressed well. So as a whole the data obtained from the development of teaching materials declared eligible, the development of learning tools refers to the modified syllabus and RPP adapted to the learning activities, evaluation results provide improvements in students' skills in writing essays. The overall quality of teaching materials that are the product of this development is categorized eligible for use of class XII students even semester.